شعـــريــــة المـــــشــــهــــد الدرامي في القصيدة الحداثية - تاوريريت, نبيلة (قــــــراءات; No 10 (2017): مجلة قراءات, 2019)
نبحث في هذا المقال على سُبل اتخاذ الشاعر الحداثي من التقنيات الدرامية (الصراع، والحوار، القناع)، أسلوبا تعبيريا، ينطلق منه في التأسيس لقصيدة حديثة، تتداخل فيها الأجناس الأدبية بعضها مع بعض، إذ يتخذ من تشعير السرد أداة تصويرية يعبر من خلالها عن تجربة شعورية خاصة، وذلك بهدف التغيير والانفلات من قبضة اللغة المتوارثة، محولا إياها إلى مشاهد درامو شعرية، تبوح بروح الجمال والشعرية، مما يؤهلها إلى مصاف التحديث.   Abstract: This article seeks to study how modernist poets use certain dramatic techniques such as conflict, dialogue, and mask,which are considered as the expressive means of the poet’s style.This latter constitutes the foundation of the modernist poetry, a common ground where different literarygenres are interwoven. The modernist poet’s poetized narrative is used as a descriptive technique so as to come to terms with a spspecific emotiona experience. The use of this stylistic technique allows the poet to achieve defamiliarization and set himself free from the inherited ruls of language. In doing so, he turns the latter into dramatically poetic scenes, which reveals the aesthetic spirit of beauty and poeticity, thue elevating it to modernity.